Experimental and statistical methods to evaluate antibacterial activity of a quaternary pyridinium salt on planktonic, biofilm-forming, and biofilm states. Issue 3 (16th March 2017) - López Pérez, Daneli; Baker, Paula J.; Pintar, Adam L.; Sun, Jirun; Lin, Nancy J.; Lin-Gibson, Sheng
Abstract: Robust evaluation and comparison of antimicrobial technologies are critical to improving biofilm prevention and treatment. Herein, a multi-pronged experimental framework and statistical models were applied to determine the effects of quaternary pyridinium salt, 4-acetyl-1-hexadecylpyridin-1-ium iodide (QPS-1), on Streptococcus mutans in the planktonic, biofilm-forming and biofilm cell states. Minimum inhibitory and bactericidal concentrations (MIC and MBC, respectively) were determined via common methods with novel application of statistical approaches combining random effects models and interval censored data to estimate uncertainties. The MICs and MBCs for planktonic and biofilm-forming states ranged from 3.12 to 12.5 μg ml −1, with biofilm values only ≈ 8 times higher. Potent anti-biofilm activity and reactive structural features make QPS-1 a promising antibacterial additive for dental and potentially other biomedical devices. Together, the experimental framework and statistical models provide estimates and uncertainties for effective antimicrobial concentrations in multiple cell states, enabling statistical comparisons and improved characterization of antibacterial agents.